Company accounting - Jubb, Peter. (Nelson, 1999)
THis book is divided into seven parts: An overview of companies and their regulation, and the financial reporting implications; Accounting for issue of securities; Recognition and measurement of financial statement elements; Reporting and disclosure; External administration; Consolidated accounts; Associates and Joint ventures.